35th Aerospace Sciences Meeting and Exhibit 1997
DOI: 10.2514/6.1997-56
|View full text |Cite
|
Sign up to set email alerts
|

Two dimensional wake vortex simulations in the atmosphere - Preliminary sensitivity studies

Abstract: A numerical large-eddy simulation model is currently being used to quantify aircraft wake vortex behavior with meteorological observables. The model, having a meteorological framework, permits the interaction of wake vortices with environments characterized by crosswind shear, stratification, and humidity. The addition of grid-scale turbulence as an initial condition appeared to have little consequence. Results show that conventional nondimensionalizations work very well for vortex pairs embedded in stably str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…Case study validations can be found in references [18,48]. The disadvantage of using the 2-D option is that it cannot realistically simulate vortex decay.…”
Section: Approach For Wake Vortex Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Case study validations can be found in references [18,48]. The disadvantage of using the 2-D option is that it cannot realistically simulate vortex decay.…”
Section: Approach For Wake Vortex Modellingmentioning
confidence: 99%
“…15,16 Vertical shear of the crosswind component can affect the descent of wake vortices and in some cases cause them to rise. 17,18 The influence of crosswind shear on vortex trajectory is being examined from our numerical modelling effort and will be described later in this paper.…”
Section: Meteorological Effectsmentioning
confidence: 99%
“…5. The case was chosen as a benchmark due to the strong rebound from the crosswind shear by the downstream vortex 34 . As apparent in Fig.…”
Section: Comparison Of Results From Fast-time Modelsmentioning
confidence: 99%
“…This predictor has shown good correlation with observations in many situations, mostly out-of-ground effect cases, but has several known limitations. Among these is the absence of vertical wind shear terms, which can prevent wakes from sinking or cause them to rise 12,13 , lack of specificity of the turbulent scale lengths required to model wake decay, an assumed hard linkage between wake sink rate and wake circulation 14 , and a rough approximation to wake decay in Figure 2 -DFW Airport Wake Sites ground effect. The in-ground-effect decay model simply applies the out-of-ground effect decay rate derived from the Greene model 10 for the first numerical interaction, then holds a constant decay rate for the remainder of the trajectory.…”
Section: Dallas-fort Worth International Airport Wakementioning
confidence: 99%
“…Numerical wake modeling with Langley's Terminal Area Simulation System (TASS) Large-Eddy Simulation model 12,15 are focused on providing the needed sensitivity studies and relationships between wake motion and decay behavior and specific atmospheric parameters.…”
Section: Wake Predictionmentioning
confidence: 99%